QTLs controlling yield and stover quality traits in pearl millet - Nepolean, T.; Blümmel, Michael; Bhasker Raj, A.G.; Rajaram, V.; Senthilvel, S.; Hash, C.T. (2006)
Preliminary assessment of genetic variability of stover quality traits and stover yield in pearl millet has demonstrated the presence of considerable variation for cell wall digestibility and stover yield (Blümmel et al. 2003). The objectives of this study are mapping QTLs for stover nutritional quality, assessing relationships among stover yield components and quality traits, and selecting target QTLs for MABC. This is the first detailed report of QTLs mapped for pearl millet stover ruminant nutritional quality traits.